2015
DOI: 10.1021/acs.nanolett.5b00251
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of GaN Nanowires with High Structural Perfection on a Metallic TiN Film

Abstract: Vertical GaN nanowires are grown in a self-induced way on a sputtered Ti film by plasma-assisted molecular beam epitaxy. Both in situ electron diffraction and ex situ ellipsometry show that Ti is converted to TiN upon exposure of the surface to the N plasma. In addition, the ellipsometric data demonstrate this TiN film to be metallic. The diffraction data evidence that the GaN nanowires have a strict epitaxial relationship to this film. Photoluminescence spectroscopy of the GaN nanowires shows excitonic transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 50 publications
9
76
0
Order By: Relevance
“…The substrate temperature was measured by a pyrometer, considering the emissivity of TiN (0.23 at this temperature) and absorption in the viewport. Reflection high‐energy electron diffraction (RHEED) revealed the pattern expected for cubic TiN, as observed by Wölz et al The growth of AlN was initiated by providing an Al flux of 1.7 × 10 14 atoms cm −2 s −1 (0.14 ML s −1 ) supplied by a conventional Knudsen cell, whereas the active N flux was not changed and corresponded to 1.03 × 10 15 atoms cm −2 s −1 (1.03 ML s −1 ). The N and Al atomic fluxes were calibrated by cross‐sectional imaging of thick GaN(0001) and AlN(0001) films, respectively, grown under slightly Ga‐ and N‐rich conditions on GaN/Al 2 O 3 (0001) substrates at 680 °C.…”
supporting
confidence: 53%
“…The substrate temperature was measured by a pyrometer, considering the emissivity of TiN (0.23 at this temperature) and absorption in the viewport. Reflection high‐energy electron diffraction (RHEED) revealed the pattern expected for cubic TiN, as observed by Wölz et al The growth of AlN was initiated by providing an Al flux of 1.7 × 10 14 atoms cm −2 s −1 (0.14 ML s −1 ) supplied by a conventional Knudsen cell, whereas the active N flux was not changed and corresponded to 1.03 × 10 15 atoms cm −2 s −1 (1.03 ML s −1 ). The N and Al atomic fluxes were calibrated by cross‐sectional imaging of thick GaN(0001) and AlN(0001) films, respectively, grown under slightly Ga‐ and N‐rich conditions on GaN/Al 2 O 3 (0001) substrates at 680 °C.…”
supporting
confidence: 53%
“…Though direct growth of semiconductor nanowires on metals was demonstrated in several material systems, such as Si, Ge, CdS, and ZnO, it was only very recently reported by Wolz et al for GaN nanowires grown on sputtered Titanium (Ti) films . However, operating III‐Nitride nanowire devices electrically integrated and directly grown on metal were not yet demonstrated to our knowledge.…”
Section: Introductionmentioning
confidence: 90%
“…16 It has been recently demonstrated that the NW growth on metal thin films helps to avoid such issues, hence reducing the potential barrier for carrier flow and allowing increased current injections with lower Joule heating. [17][18][19][20][21] As many efforts have been made in the UV III-nitride NW community to bring NW technology to a practical application, it is of particular importance to study the diode T j of such devices to evaluate the best configuration for efficient heat dissipation through the heat sink substrate, prevent overheating, short lifespan, and reduced light intensity. To date, there are no reports on UV AlGaN (and in general IIInitride) NWs LED T j measurements; therefore, this work consists of experimental findings that aim to enlighten the UV LED NW community for designing and optimizing the diode structures and substrate and to realize high power and reliable devices for eventual practical implementation.…”
Section: Introductionmentioning
confidence: 99%